Genetic recombination-mediated evolutionary interactions between phages of potential industrial importance and prophages of their hosts within or across the domains of Escherichia, Listeria, Salmonella, Campylobacter, and Staphylococcus - Saba Kobakhidze; Stylianos Koulouris; Nata Kakabadze; Mamuka Kotetishvili (BMC Microbiology, 2024)
Abstract Background The in-depth understanding of the role of lateral genetic transfer (LGT) in phage-prophage interactions is essential to rationalizing phage applications for human and animal therapy, as well as for food and environmental safety. This in silico study aimed to detect LGT between phages of potential industrial importance and their hosts. Methods A large array of genetic recombination detection algorithms, implemented in SplitsTree and RDP4, was applied to detect LGT between various Escherichia, Listeria, Salmonella, Campylobacter, Staphylococcus, Pseudomonas, and Vibrio phages and their hosts. PHASTER and RAST were employed respectively to identify prophages across the host genome and to annotate LGT-affected genes with unknown functions. PhageAI was used to gain deeper insights into the life cycle history of recombined phages. Results The split decomposition inferences (bootstrap values: 91.3–100; fit: 91.433-100), coupled with the Phi (0.0-2.836E-12) and RDP4 (P being well below 0.05) statistics, provided strong evidence for LGT between certain Escherichia, Listeria, Salmonella, and Campylobacter virulent phages and prophages of their hosts. The LGT events entailed mainly the phage genes encoding for hypothetical proteins, while some of these genetic loci appeared to have been affected even by intergeneric recombination in specific E. coli and S. enterica virulent phages when interacting with their host prophages. Moreover, it is shown that certain L. monocytogenes virulent phages could serve at least as the donors of the gene loci, involved in encoding for the basal promoter specificity factor, for L. monocytogenes. In contrast, the large genetic clusters were determined to have been simultaneously exchanged by many S. aureus prophages and some Staphylococcus temperate phages proposed earlier as potential therapeutic candidates (in their native or modified state). The above genetic clusters were found to encompass multiple genes encoding for various proteins, such as e.g., phage tail proteins, the capsid and scaffold proteins, holins, and transcriptional terminator proteins. Conclusions It is suggested that phage-prophage interactions, mediated by LGT (including intergeneric recombination), can have a far-reaching impact on the co-evolutionary trajectories of industrial phages and their hosts especially when excessively present across microbially rich environments.